Application of Accounting for Islamic Boarding School Business Unit: Study on Ma’had Al-Muqoddasah Li Tahfidhil Qur’an Model - Faradisi, Roghiebah Jadwa; Anggara, Fajar Surya Ari (Al Tijarahh, 2022)
Islamic boarding schools are religious, educational institutions that should provide decent quality infrastructure facilities of economic facilities such as cooperative Islamic boarding schools. A boarding school cooperative is a monetary institution engaged in the scope of Islamic boarding schools that is required to be able to implement financial management properly. Proper financial management can be realized with good financial reports and following applicable Accounting Standards. Often Islamic boarding school cooperatives do not pay much attention to financial management in depth due to limited knowledge and experience in financial reporting. In fact, financial reports greatly affect financial management in Islamic boarding school cooperatives. This study aims to examine how the practical accounting application and its compliance with accounting standards in the financial administration section of Ma’had Al-Muqoddasah Li Tahfidhil Qur’an Ponorogo, as well as to find out the importance of accounting for an institution. This research uses qualitative descriptive research methods with interviews, observations, and documentation. Accounting for Islamic boarding schools is a process of preparing financial statements, in general, to produce financial information by considering the characteristics and nature of Islamic boarding schools. The findings of this study reveal that the accounting contained in the financial administration department of Ma’had Al-Muqoddasah Li Tahfidhil Qur’an Ponorogo has implemented accounting even though it is not perfect. The need to improve accounting to be under applicable accounting standards by learning and evaluating the reports that have been applied